Development of microgap and nanogap automated permittivity measurement system - Azizullah, Saifullah (Universiti Malaysia Perlis (UniMAP), 2012)
The goal of this research is to develop an electronic system that integrated with nanogap capacitor biosensor. This system is called Permittivity Measurement System (PMS). It measures the impedance value of the nanogap capacitor and calculates the permittivity value based on the parameter specification of nanogap capacitor obtained through characterization process. The parameters are gap width, internal resistance, capacitance value with no sample, and cross section area of the plate. One sample of nanogap and ten samples of microgap capacitor are characterized. Five components combined to create PMS. The first component is the sinusoidal wave generator and the technique that employed for sinusoidal wave generation is the digital approximation sinusoidal wave generation technique. The output frequency range is from 10Hz until 1kHz and the output peak to peak voltage is 6V to -6V. The second component is the low pass filter. This component is used for filtering the noise from sinusoidal wave. MAX262 programmable universal active filter is selected as the low pass filter. The third component that creates PMS and has contact with the nanogap capacitor is the impedance measurement unit. The auto balancing bridge method is employed to measure the impedance value of the nanogap capacitor. A range circuit with eight level of selection is added to wider the impedance measurement range. The amplitude of the sinusoidal wave that applied to the nanogap capacitor is 200mV. The fourth component is the phase differential measurement unit. It is responsible to measure the phase difference between current and voltage wave. The fifth and the main component of PMS is the XScale-Mini SBC. It is responsible to control, capture, and analyze signal from the other component of PMS. Visual C++ is used to develop the software part of XScale-Mini SBC. The current wave, voltage wave, and also the output phase differential is captured and analyzed. All the circuits are tested and the produced signals is shown and discussed. The test shows that PMS is capable to measure up to 85% of accuracy. The simulation for the electrical model of DNA during immobilization and hybridization is performed. The fabricated circuit is tested through the measuring of micro and nanogap capacitance.